Analysis of the South African automotive retailers in an economic downturn using the resource based view - Streicher, Hartogh (2013)
The cyclical nature of the automotive industry has been blamed for many dealership closures as well as thousands of retrenchments. Macro environmental changes like the recent spike in oil prices and the sub-prime debacle can have a detrimental effect on the automotive retailers and be partially blamed for the closures and retrenchments. This results in a continuously changing external environment which might necessitate subsequent internal changes. These changes might involve physical resources like people, demographics, products and materials or non-tangible resources like policies, procedures and the way business is conducted and personnel are treated. The management style and methodologies of automotive retail are predominantly based on control of annual budgets and are therefore not pro-active and unable to cope with sudden and drastic changes like the recent global economic decline. The primary aim of this research is to do an explanatory study to determine whether senior managers in the automotive retail sector has identified their key resources and if they can leverage the application thereof to enable a sustainable competitive advantage. The secondary aim is to determine if these resources or the application thereof change during an economic decline. The research was conducted by means of multiple and in-depth semi-structured case studies of twelve dealers in the Gauteng area. This method is generally accepted as a technique to properly diagnose the current scenario and to evaluate the situation according to relevant theory. The results of this research shows that the automotive retail sector has not yet embraced the resource based view, can not recognise all their key resources, and do not actively cultivate resources for future utilisation. By creating resource awareness the recognition and application of resources might become more dynamic which can make the industry more resilient in future economic downturns which might result in less closures and retrenchments during future economic declines. === Dissertation (MBA)--University of Pretoria, 2010. === Gordon Institute of Business Science (GIBS) === unrestricted